Pelatihan Membaca Al-Qur’an dan Metode At-Tartil di Pondok Sabilul Huda - Muhamad Khoirur Roziqin; Ospa Pea Yuanita Meishanti; Muhammad Khoirul Niam (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2021)
In Sabilul Huda's accommodation this year there were new students who came to the lodgings, most of the new students had not been able to read the Koran properly, from there after analyzing the situation the researchers had the idea of ​​carrying out new activities for new students so they could read the Koran. with the at-tartile method. This approach method for implementing community service activities includes lectures, discussions, and workshops (training). Provides additional knowledge for all students in the importance of reading Al-Qur'an and the At-tartil method. The results of this service can foster enthusiasm for the students in improving their skills in their daily needs